1997
DOI: 10.1007/bf02406163
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere microbial populations in contaminated soils

Abstract: Abstract. Rhizosphere microbial populations may increase bioremediation of soil contaminated with organic chemicals. A growth chamber study was conducted to evaluate rhizosphere microbial populations in contaminated and non-contaminated soil. Alfalfa (Medicago sativa L.) and alpine bluegrass (Poa alpina L.) were grown in soil containing a mixture of organic chemicals for 14 weeks. The equal millimolar mixture of hexadecane, (2,2-dimethylpropyl)benzene, cis-decahydronaphthalene (decalin), benzoic acid, phenanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
65
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(76 citation statements)
references
References 27 publications
7
65
0
1
Order By: Relevance
“…Numerous studies have demonstrated the importance of the rhizosphere effect on degradation of organic contaminants. Most of these studies have examined terrestrial plants and agricultural chemicals (1,2,27); few have looked at the influence of plant-associated microorganisms on the fate of PCBs (15,16) and PAHs (34,39). There have been a limited number of studies on PAH degradation involving wetland or salt marsh ecosystems, but none have studied the diversity of PAH-degrading microorganisms present (28,30,49).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the importance of the rhizosphere effect on degradation of organic contaminants. Most of these studies have examined terrestrial plants and agricultural chemicals (1,2,27); few have looked at the influence of plant-associated microorganisms on the fate of PCBs (15,16) and PAHs (34,39). There have been a limited number of studies on PAH degradation involving wetland or salt marsh ecosystems, but none have studied the diversity of PAH-degrading microorganisms present (28,30,49).…”
Section: Discussionmentioning
confidence: 99%
“…At higher TPH concentrations microbes have a faster metabolic rate due to the presence of excess carbon as a food source (Nichols et al, 1996). This high level of metabolic activity may have influenced the numbers of microbes catalogued in this experiment in two ways.…”
Section: Discussionmentioning
confidence: 99%
“…Various grasses and leguminous crops were used for rhizoremediation because of the profound root biomass [7]. The establishment of crop cover also improves the soil physical and chemical properties of contaminated soil and increase the contact microbes and contaminants [15].…”
Section: Introductionmentioning
confidence: 99%